1992
DOI: 10.1200/jco.1992.10.9.1452
|View full text |Cite
|
Sign up to set email alerts
|

Sequential administration of interleukin-3 and granulocyte-macrophage colony-stimulating factor following standard-dose combination chemotherapy with etoposide, ifosfamide, and cisplatin.

Abstract: We conclude that after conventional-dose VIP chemotherapy, a shortened treatment course of IL-3 (5 days) sequentially followed by GM-CSF (10 days) combines the benefits of prolonged single GM-CSF treatment on WBC count recovery in all patients and an accelerated platelet recovery only in some intensively pretreated patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
57
2

Year Published

1994
1994
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(64 citation statements)
references
References 16 publications
5
57
2
Order By: Relevance
“…Differences in the quantitative recruitment of hematopoietic progenitors in the bloodstream achieved by different mobilization schedules might be dependent on the relative frequency of CD34 + subpopulations that are not clonogenic in short-term culture assay systems, such as lymphoid progenitors as well as primitive progenitors and stem cells. 12,13 We found that CD34 + cells from the G-CSF group had a significantly lower plating efficiency than CY+G-CSF mobilized CD34 + cells. This finding associated with the significantly lower numbers of LTC-IC detected in the G-CSFmobilized products suggests that the lower clonogenicity of CD34 + cells observed in G-CSF-mobilized patients was likely to be due to the mobilization of mature CD34 + cells which are not detected in the CFU-Mix assay.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Differences in the quantitative recruitment of hematopoietic progenitors in the bloodstream achieved by different mobilization schedules might be dependent on the relative frequency of CD34 + subpopulations that are not clonogenic in short-term culture assay systems, such as lymphoid progenitors as well as primitive progenitors and stem cells. 12,13 We found that CD34 + cells from the G-CSF group had a significantly lower plating efficiency than CY+G-CSF mobilized CD34 + cells. This finding associated with the significantly lower numbers of LTC-IC detected in the G-CSFmobilized products suggests that the lower clonogenicity of CD34 + cells observed in G-CSF-mobilized patients was likely to be due to the mobilization of mature CD34 + cells which are not detected in the CFU-Mix assay.…”
Section: Discussionmentioning
confidence: 78%
“…[1][2][3]5,12,13,22 Both chemotherapy or growth factors used alone expand the pool of circulating progenitors and, when combined, exert a significantly higher effect. 3,4 Fol- lowing CY+G-CSF administration, circulating CD34 + cells and committed progenitors initially decrease to undetectable levels, while reappearing together with the more primitive LTC-IC at the time of leukocyte recovery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the relatively low burden of the harvest proce dure may explain the increased popularity of PBSC. Fur thermore, total costs of PBPC autografting are lower than those of ABMT [69], Peripheral blood stem cells can be mobilised by chemotherapy [70][71][72], chemotherapy followed by HGFs [73][74][75] and HGFs alone [76][77][78][79]. Despite the increasing knowledge of progenitor-stroma interaction, the mechanisms of stem cell mobilisation remain undefined.…”
Section: Peripheral Stem Cell Transplantation In Haematology and Oncomentioning
confidence: 99%
“…Moreover, mobilization with disease-oriented chemotherapy in addition to cytokines is particularly recommended in patients with chemosensitive neoplasms as the greater efficacy of mobilization is combined with the anti-tumour effect of the drug. In fact, in most CPC transplantation programmes the mobilizing regimens include agents (often at high doses) with proven efficacy against the underlying disease (Brugger et al, 1992;Shimazaki et al, 1992;Gianni AM et al, 1995).…”
mentioning
confidence: 99%